Cloning, expression, and nucleotide sequence of genes involved in production of lactococcin DR, a bacteriocin from lactococcus lactis subsp. lactis. - Rince, A (1994)
The partial nucleotide sequence of a Lactococcus lactis subsp. lactis ADRIA 85LO30 bacteriocin-producing operon was determined. The first two open reading frames of the operon are necessary to get bacteriocin expression in L. lactis IL1403R.